2014
DOI: 10.14735/amko2014434
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma in Localized Scleroderma

Abstract: klinika LF MU a FN u sv. Anny v Brně 2 Klinika komplexní onkologické péče, Masarykův onkologický ústav, Brno 3 I. patologicko-anatomický ústav, LF MU a FN u sv. Anny v Brně Súhrn Popisujeme prípad mladej pacientky, u ktorej došlo k vzniku ulcerácií na pravej nohe v teréne 15 rokov trvajúcej ložiskovej sklerodermie (LS, morfey). Podľa CT vyšetrenia a RTG bol nález zhodnotený ako osteomyelitída a pacientka bola liečená kombináciou antibio tík. Opakované histologické vyšetrenia zo spodiny vredu preukázali granula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although a malignant turn of localized scleroderma is rarely seen, Durcanska et al concluded that a young 26-year-old woman who was diagnosed with localized scleroderma (morphea) ultimately developed SCC camouflaged by osteomyelitis on the lower extremities after a long course of the disease [9]. An 18-year-old woman with progressive SSc developed SCC of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Although a malignant turn of localized scleroderma is rarely seen, Durcanska et al concluded that a young 26-year-old woman who was diagnosed with localized scleroderma (morphea) ultimately developed SCC camouflaged by osteomyelitis on the lower extremities after a long course of the disease [9]. An 18-year-old woman with progressive SSc developed SCC of the skin.…”
Section: Discussionmentioning
confidence: 99%